PERAN EKONOMI ISLAM DALAM MEMBERDAYAKAN EKONOMI PEREMPUAN - Adriani A; Oktaviani O (Fakultas Hukum Universitas Malikussaleh, 2023)
Empowering women is one of the keys to increasing a country's national income and can affect the country's progress. To support this statement, reported by BPS Indonesia, the female population in Indonesia will reach 49.42 percent by 2020, which means that women have the opportunity to advance the nation if properly and appropriately empowered. Islam as a religion has its own economic concept which is now often termed Islamic economics or Islamic economics. The concept of Islamic economics talks about two things, firstly about the legal status of economic transactions, and secondly about who can carry out these transactions. What's interesting about this is that since the beginning of its development, Islam has never closed space for women and men to develop in the economic sector. As said by the wife of the prophet Muhammad SAW, Khadijah where he was a trader. Departing from that this research discusses the role of women in Islam in an effort to build the economy. Normative research is library research, in which the author will examine library materials or secondary data as the basic material for research. The nature of this research is descriptive, namely describing how the position of Islamic religious doctrine is in women's economic empowerment. Data collection method is done by documentation. Furthermore, the approach used in this study is a doctrinal approach, namely research conducted by examining all Islamic legal regulations related to the issues studied. The research results show that women in Islam are given equal space to play a role in the economy.